Approach to the Problem of Bio-Inspired Robotic Gripper Designing - Kumicakova, Darina; Konecny, Zdenek (Communications - Scientific Letters of the University of Zilina, 2014)
The article with its content belongs to the field of bio-inspired robotics. This main focus is aimed at the problem of a specialised human-like robotic gripper designing. The article presents our approaches to solution of the chosen problems of multifunctional robotic grippers designing on the example of a proposed 3D model of three-fingered bio-robotic gripper. Attention is devoted to utilisation of CAD/CAE tools for exploring characteristics of the design using computer simulation.
Keywords: bio-inspired robots; object grasping; computer simulation; CAD/CAE; contact analyses